Title: Aegean, Arctic Title Vads Collection: Design Council Slide Collection - Manufacturer: Design Animations Ltd Designer: Robins, George (1972)
Description: Elements from the picture framing systems designed by George Robins for Design Animations Ltd. and winner of the Duke of Edinburgh's Design Prize in 1973: the 'Arctic' and 'Aegean' systems using clear acrylic trays and three variant of system using extruded aluminium frames.